STRATEGY FOR DEVELOPING THE MARINE OPERATIONS EDUCATION COMMAND (KODIKOPSLA) TO IMPROVE THE ROLE IN PREPARING EXCELLENT HUMAN RESOURCES FOR THE INDONESIAN NAVY - Rifky Najib; Ahmadi Ahmadi; Joko Purnomo (JOURNAL ASRO, 2021)
The development of the strategic environment, especially in the fields of science and technology, requires the Indonesian Navy to prepare strategies to deal with these challenges. In addition to the readiness of the defense equipment, the human resources of the crew must also be superior and professional. The Marine Operations Education Command (Kodikopsla) is an educational institution for the Indonesian Navy which is the center for marine operations education. The purpose of this study was to determine an alternative Kodikopsla development strategy in order to increase its role in preparing superior Indonesian Navy human resources by using the integration of the SWOT, ANP and Balanced scorecard methods. The results of environmental identification in Kodikopsla contained 16 (sixteen) internal factors with 6 (six) strength factors and 10 (ten) weakness factors, and 15 (fifteen) external factors with 9 (nine) opportunity factors and 6 (six) threat factors. . By weighting the EFE and EFI metrics, the chosen strategy is the WO Strategy which means maximizing the improvement of weakness factors for exploiting opportunities. From the results of the weighting calculation using the ANP method, it is obtained that the WO1 priority strategy with a weight of 0.3851. Furthermore, 15 (fifteen) strategic targets were produced which were divided into 4 (four) BSC perspectives, namely financial, internal business, customer and learning and growth as well as determining the Key Performance Indicators (KPI) of each strategic target as the basis for strategy mapping Keywords: Kodikopsla, SWOT Method, ANP, Balanced Scorecard, Key Performance Indicator